CASE STUDY OF SOLAR ENERGY - MISS. PATIL POONAM SAMBHAJI; MISS. PATIL SHITAL SARJERAO; MISS. BHOSALE SUNITA SHIVAJI (International Journal of Innovations in Engineering Research and Technology, 2021)
To study the efficiency increasing of electric energy generation in the Photovoltaic System is concentrated on this paper. There are four cases to improve the efficiency of power producing from the Photovoltaic System. This article not only describes the differences of facilities before and after the proposal, but also evaluates the electric energy generation efficiency and improved results for each proposal. Finally, the better efficiency of all improving ways is analyzed to get into conclusions in order to provide further improvement and reference for the industry in the future. Overall, these proposed methods can improve the efficiency of solar photovoltaic electric energy generation in about 30.18%.